#PapuanLivesMatter in the Wake of #BlackLivesMatter: Relations of Collective Identity in Twitter Activism - Yasmine Anabel Panjaitan; Lulu Nurul Janah (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2022)
Collective identity, or a sense of ‘we-ness’ in relation or contrast with one another, is a crucial feature of social activism. Especially considering the rise of intersectional movements in today’s era, it is important to look into the role of collective identity in shaping online movements. This article intends to unravel the relations of collective identity in the Twitter activism #PapuanLivesMatter that emerged in the wake of #BlackLivesMatter. Thirteen tweets that carry the hashtags #PapuanLivesMatter and #BlackLivesMatter, either separately or together, were analyzed. The theory of appraisal from Martin and White was applied to identify how the tweets enact relations of collective identity by looking into the implicit and explicit evaluation of the text that relies on positive and negative classifications. The results show that the relations of collective identity in #PapuanLivesMatter during the rise of #BlackLivesMatter are congruent at the broad level and divergent at the group level. At the broad level, #PapuanLivesMatter and #BlackLivesMatter address the same issues and collectively work toward raising awareness for discrimination against black lives. Although #PapuanLivesMatter still maintains its representation of discrimination at the group level, it propagates ideologies and objectives that are exclusively directed for West Papuan causes, namely ethnic discrimination and political self-determination.